C(sp3)–H Bond Acylation with N-Acyl Imides under Photoredox/ Nickel Dual Catalysis - Kerackian, Taline; Reina, Antonio; Krachko, Tetiana; Boddaert, Hugo; Bouyssi, Didier; Monteiro, Nuno; Amgoune, Abderrahmane (Synlett, 2020)
A novel Ni/photoredox-catalyzed acylation of aliphatic substrates, including simple alkanes and dialkyl ethers, has been developed. The method combines C–N bond activation of amides with a radical relay mechanism involving hydrogen-atom transfer. The protocol is operationally simple, employs bench-stable N-acyl imides as acyl-transfer reagents, and permits facile access to alkyl ketones under very mild conditions.
Keywords: nickel catalysis; photocatalysis; acylation; radical relay; C–N bond activation; ketones